Aberrant dynamic structure–function relationship of rich‐club organization in treatment‐naïve newly diagnosed juvenile myoclonic epilepsy. Issue 12 (13th April 2022) - Liu, Guangyao; Zheng, Weihao; Liu, Hong; Guo, Man; Ma, Laiyang; Hu, Wanjun; Ke, Ming; Sun, Yu; Zhang, Jing; Zhang, Zhe
Abstract: Neuroimaging studies have shown that juvenile myoclonic epilepsy (JME) is characterized by impaired brain networks. However, few studies have investigated the potential disruptions in rich‐club organization—a core feature of the brain networks. Moreover, it is unclear how structure–function relationships dynamically change over time in JME. Here, we quantify the anatomical rich‐club organization and dynamic structural and functional connectivity (SC–FC) coupling in 47 treatment‐naïve newly diagnosed patients with JME and 40 matched healthy controls. Dynamic functional network efficiency and its association with SC–FC coupling were also calculated to examine the supporting of structure–function relationship to brain information transfer. The results showed that the anatomical rich‐club organization was disrupted in the patient group, along with decreased connectivity strength among rich‐club hub nodes. Furthermore, reduced SC–FC coupling in rich‐club organization of the patients was found in two functionally independent dynamic states, that is the functional segregation state (State 1) and the strong somatomotor‐cognitive control interaction state (State 5); and the latter was significantly associated with disease severity. In addition, the relationships between SC–FC coupling of hub nodes connections and functional network efficiency in State 1 were found to be absent in patients. The aberrant dynamic SC–FC coupling of rich‐club organization suggests a selective influence of densely interconnected network core in patients with JME at the early phase of the disease, offering new insights and potential biomarkers into the underlying neurodevelopmental basis of behavioral and cognitive impairments observed in JME. Abstract : We quantified the anatomical rich club organization and dynamic structural and functional connectivity coupling in treatment‐naïve newly diagnosed patients with JME. Our results showed that the anatomical rich club organization was disrupted in the patient, along with reduced structural and functional connectivity coupling in two functionally independent dynamic states.